2017
DOI: 10.21037/atm.2017.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Lighted ureteral stents in laparoscopic colorectal surgery; a five-year experience

Abstract: Background: Ureteral injuries during colorectal surgery are a rare event, ranging in the literature from 0.28-7.6%. Debate surrounds the use of prophylactic lighted ureteral stents to help protect the ureter during laparoscopic surgery. It has been suggested that they help to identify injuries but do not prevent them. The authors look to challenge this.Methods: Over 66 months, every laparoscopic or colectomy involving ureteral stents was recorded. Researchers documented any injury to the ureter intraoperativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 8 publications
(10 reference statements)
2
34
0
Order By: Relevance
“…The use of lighting devices has been explored in medicine for years. In colorectal and gynecological surgeries, for example, iatrogenic ureteric injury is a serious complication with a variable incidence between 0.7-10% [14]. The identification of ureters is challenging and the optional double J stent placement is invasive and associated with serious adverse events [15];however, the use of fluorescence and lighted ureteral stents has overcome these problems.…”
Section: Discussionmentioning
confidence: 99%
“…The use of lighting devices has been explored in medicine for years. In colorectal and gynecological surgeries, for example, iatrogenic ureteric injury is a serious complication with a variable incidence between 0.7-10% [14]. The identification of ureters is challenging and the optional double J stent placement is invasive and associated with serious adverse events [15];however, the use of fluorescence and lighted ureteral stents has overcome these problems.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that prophylactic LUS placement in laparoscopic colectomy is a safe procedure. Boyan et al 15) reported a total of 465 laparoscopic colorectal resections with prophylactic LUS. No IUI occurred.…”
Section: Prevention Of Iatrogenic Ureteral Injury In Colorectal Surgerymentioning
confidence: 99%
“…It was also advocated that LUS insertion might save time in the operating room by simplifying the ureter identification procedure and, in cases of injury, avoiding complex interventions. Considering the operative time required for injury identification and repair, the LUS insertion procedure itself is time-effective, requiring approximately 11-28 min, depending on the length of the procedure and coordination arrangements 6,14,15) .…”
Section: Prevention Of Iatrogenic Ureteral Injury In Colorectal Surgerymentioning
confidence: 99%
“…Lighting devices for surgical guidance have been investigated for years with good results. In laparoscopic colorectal and gynecological surgeries, the use of lighted ureteral stents successfully prevented iatrogenic injuries [14,15]. In ophthalmologic procedures, light-emitting diode (LED) technology is used for vitrectomy, with the advantage of no thermal or photodynamical harm; this provides better illumination than other light sources [16,17].…”
Section: Introductionmentioning
confidence: 99%